Usi intelligenti dell’intelligenza artificiale. Il man-with-the-machine learning - Roberto Trinchero (Journal of Educational, Cultural and Psychological Studies)
INTELLIGENT USES OF ARTIFICIAL INTELLIGENCE. THE MAN-WITH-THE-MACHINE LEARNING